Combat Exposure Severity Is Associated With Reduced Cortical Thickness in Combat Veterans: A Preliminary Report. (August 2017) - Averill, Lynnette A.; Abdallah, Chadi G.; Pietrzak, Robert H.; Averill, Christopher L.; Southwick, Steven M.; Krystal, John H.; Harpaz-Rotem, Ilan
Background: Chronic stress and related physiological responses are known to have deleterious effects on neural integrity. Combat exposure is a notoriously pathogenic stressor, and with over 2 million U.S. troops deployed to active combat zones since 2001, there is an urgent need to advance our understanding of its potential neural impact. Previous evidence suggests structural alterations in posttraumatic stress disorder (PTSD) and more recent studies have explored cortical thinning specifically. This preliminary study investigates the impact of combat exposure on cortical thickness, controlling for history of early life stress and age. Methods: Twenty-one combat-exposed Veterans with PTSD and 20 non-PTSD combat-exposed controls (mean age 32.7) completed the Combat Exposure Scale, Childhood Trauma Questionnaire, and structural magnetic resonance imaging in a Siemens 3T TIM trio system. General linear model was used to examine the effect of combat exposure on cortical thickness, controlling for early life trauma exposure and age using cluster-wise correction ( p < 0.05). Results: This preliminary study found a negative correlation between combat exposure severity (CES) and cortical thickness in the left superior temporal and left rostral middle frontal regions, as well as an interaction between PTSD diagnosis status and CES, in the superior temporal/insular region showing a stronger negative correlation between CES and cortical thickness in the non-PTSD group. Conclusions: Though caution should be taken with interpretation given the preliminary nature of the findings, the results indicate combat exposure may affect cortical structure beyond possible alterations due to early life stress exposure or PTSD psychopathology. Though replication in larger samples is required, these results provide useful information regarding possible neural biomarkers and treatment targets for combat-related psychopathology as well as highlighting the pathogenic effects of combat.